2022
DOI: 10.1109/access.2022.3211072
|View full text |Cite
|
Sign up to set email alerts
|

Virtual LiDAR Simulation as a High Performance Computing Challenge: Toward HPC HELIOS++

Abstract: Performance measurements on the FinisTerrae-II supercomputer were possible thanks to the CESGA (Galician supercomputing center).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The advantage of the ray-tracing method [6][7][8] lies in its ability to accurately simulate the propagation and scattering process of light, as well as generate high-precision ground object echo signals. However, when dealing with complex scenes, the calculation load of ray tracing significantly increases due to multiple reflections of light, resulting in low simulation efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of the ray-tracing method [6][7][8] lies in its ability to accurately simulate the propagation and scattering process of light, as well as generate high-precision ground object echo signals. However, when dealing with complex scenes, the calculation load of ray tracing significantly increases due to multiple reflections of light, resulting in low simulation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the corresponding reflected angle (θ r ) is obtained. By utilizing Equation (8), the value of f sur (θ i , θ r ) is calculated, which represents the reflectance function for light energy. Finally, substituting f sur (θ i , θ r ) into Equation (4) allows us to determine Q out , representing the reflected light energy.…”
Section: Surface Light Energy Reflectance Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that LiDAR simulators may benefit from high-performance computing (HPC) algorithms or techniques. For instance, using HELIOS++ as a case study, novel algorithms run on parallel computers boost the performance [37]. It is worth further investigating how the LESS LiDAR simulator can benefit from these algorithms or techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it supports detailed XML specifications for different platforms and scanners. Instead of a ray tracing implementation similar to the native ray tracing of computer games such as Grand Theft Auto V (GTA V) and 3D graphics software such as Blender, HELIOS++ provides an efficient object-aware ray tracing algorithm that supports the high-performance parallel computation of different physical models on the light ray (Esmorís et al, 2022).…”
Section: Virtual Laser Scanningmentioning
confidence: 99%